What Drive the Damage to Post-Merger Operating Performance? - Soegiharto, Soegiharto (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
This study examines whether biddersâ post-merger operat-ing performance are affected by their CEO behavior, premiumspaid to the target firms, the period of mergers, the method ofpayment, the industry of merged firms, capital liquidity, andtheir pre-merger operating performance. Testing the U.S. suc-cessful merger and acquisition data for the period of 1990s, thisstudy finds that in-wave mergers, intra-industry mergers, thepayment of lower premiums, and better pre-merger operatingperformance drive the bidders to produce better post-mergeroperating performance. Three measures of CEO behaviorâthemain predictor scrutinezed in this studyâare proposed andexamined, and the results demonstrate that the effects of thesemeasures on post-merger operating performance are mixed,suggesting that each of the behavioral measures designed in thisstudy may capture CEO behavior in different ways.Keywords: capital liquidity; CEO overconfidence; merger waves, method of pay-ment operating performance